Foreign direct investment & petty corruption in Sub-Saharan Africa: An empirical analysis at the local level - Julian Donaubauer; Peter Kannen; Frauke Steglich (Kiel Centre for Globalization (KCG), 2019)
Inspired by a recent and ongoing debate about whether foreign direct investment (FDI) represents a blessing for or an impediment to economic, social, and political development in FDI host countries this paper addresses two issues: Does the presence of foreign investors impact the occurrence of petty corruption? If so, what are the main underlying mechanisms? Geocoding an original firm-level dataset and combining it with georeferenced household survey data, this is a first attempt to analyze whether the presence of foreign investors is associated with changes in local corruption around foreign-owned production facilities in 19 Sub-Saharan African countries. Applying an estimation strategy that explores the spatial and temporal variation in the data, we find strong and consistent evidence that the presence of foreign firms increases bribery among people living nearby. When examining two potential channels, we find no support that FDI-induced economic activity leads to more corruption. In contrast, the results provide evidence that FDI affects corruption via norm transmission.
Keywords: D1; F21; F23; O12; 330; FDI; corruption; georeferenced data; Sub-Saharan Africa